2010
DOI: 10.1007/s12020-010-9408-3
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones are positively associated with insulin resistance early in the development of type 2 diabetes

Abstract: Thyroid hormones have generally been found normal in diabetic patients. The question of whether variation within the euthyroid range influences insulin sensitivity in type 2 diabetes remains to be established. To investigate this, a meal was given to four groups: 17 healthy volunteers (controls), 22 first-degree relatives of type 2 diabetic subjects (relatives), 15 subjects with impaired glucose tolerance (IGT), and 24 subjects with overt type 2 diabetes (DM). Blood was drawn for 360 min for measurements of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 21 publications
9
90
1
3
Order By: Relevance
“…HT-associated complications have become a concerning issue, as metabolic disturbances such as dyslipidemia and insulin resistance have been demonstrated in even subclinical HT patients (euthyroid level) [Lambadiari et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…HT-associated complications have become a concerning issue, as metabolic disturbances such as dyslipidemia and insulin resistance have been demonstrated in even subclinical HT patients (euthyroid level) [Lambadiari et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the mutual association with body composition, there may also be a direct link between thyroid function and glucose metabolism. With regard to thyroid dysfunction, both hyper-and hypothyroidism have been reported to be associated with IR (17). This apparent paradox may result from the differential effects of thyroid hormones at the level of the liver (insulin antagonistic) and peripheral tissues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both hyper-and hypothyroidism have been reported to be associated with insulin resistance (IR) (17). Moreover, administration of T 3 to normal volunteers results in IR (18).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenetic mechanism can be explained by insulin resistance and metabolic derangement [414]. A study showed that patients on treatment for hyperthyroid Graves' disease were almost twice as likely to develop type 2 diabetes than the general population, although they were less likely to be overweight and were less likely to have family history.…”
Section: Epidemiologymentioning
confidence: 99%